Developing functional epoxy/graphene composites using facile in‐situ mechanochemical approach. Issue 13 (3rd February 2023) - Meng, Qingshi; Feng, Yuanyuan; Han, Sensen; Yang, Fei; Demiral, Murat; Meng, Fanze; Araby, Sherif
Abstract: The awareness of developing eco‐friendly polymer composites via green chemistry attract much attention in the recent years. In the current work, we explore preparing functional epoxy/ graphene nanocomposites using mechanochemical approach. Graphene platelets (GnPs) were modified with long‐chain surfactant via high‐energy ball milling. Modified‐GnPs (m‐GnPs) promote the dispersion quality and interface strength with epoxy matrix leading to higher mechanical properties, and better electrical and thermal conductivity compared to unmodified GnPs system. At 2.0 vol% m‐GnPs, elastic modulus, tensile strength, and thermal conductivity of epoxy were improved by 889%, 163%, and 105%, respectively. In addition, percolation threshold of electrical conductivity was observed at 0.71 vol% m‐GnPs. Halpin‐Tsai micromechanical model was able to predict the elastic modulus of the epoxy/GnP nanocomposites. The model results were compared experimental measurements. Furthermore, the measurements showed epoxy/m‐GnP film possess high sensitivity to mechanical strains and impact loads. The current work gives a step forward to use mechanochemistry approach in the production of functional epoxy/graphene composites. Abstract :